THE INFLUENCE OF SCHOOL ENVIRONMENT AS THE SOURCE OF LEARNING PROCESS UNDER THE THEME OF ECOSYSTEMS WITH PROBLEM BASED LEARNING MODEL TOWARDS SCIENTIFIC BEHAVIOR OF THE STUDENTS - Alfiyah, Anis; Parmin, Parmin; Khusniati, Miranita (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ Based on observations and interviews in SMP N 1 Sumber obtained information that scientific attitude of students is still low. Another obstacle that teacher don’t take advantage of school environment as source of learning. This can to cause the student’s learning results are low. The various constraints experienced in science learning can be addressed by applying the model of learning and source of learning, it is exploiting of school environment as source of learning with learning model Problem Based Learning. This study aimed to determine the influence of the exploiting of school environment as source of learning with learning model Problem Based Learning towards student’s cognitive learning results and scientific attitude of student.The study design was quasi experimental design of nonequivalent control group design. The sample was taken by using purposive sampling technique which is resulted in class VII B as experimental class and class VII A as control class. The data consists of the posttest value and the observation of scientific attitude of student by observer. The result of this study showed that average of posttest value experiment class is 79.34 and control class is 69.76. The resulted of biserial correlation analysis is 0.663 and coefficient of determination is 44%. Therefore, the exploiting of school environment as source of learning by Problem Based Learning model on cognitive learning was resulted with the strong category. Based on the observation, the resulted of spearman correlation analysis is 0,684 and the resulted of coefficient of determination is 47%.Therefore, the exploiting of school environment as source of learning with learning model Problem Based Learning effect on scientific attitude of student with the strong category.